Leadership style from perspective of the hospital's administrators and their employees - Miri, Farzane; Shahabi, Nahid; Asadipour, Elahe (Researcher Bulletin of Medical Sciences, 2018)
Introduction: Leadership style is one of the most important elements of leadership or management position in labor industries. Leadership style is not how a manager or leader behaves in a given situation, but also how other employees and subordinates understand a behavior. Leadership style of a manager is a field in which such differences may occur easily. Therefore, managers not only should pay attention to the exact perception, but also predict other perception and be able to properly respond in different situations. Material and Methods: The statistical sample consists of 18 senior executives (manager and matron) of teaching hospitals and 125 middle managers at clinical and administrative departments of hospitals. Data collection tool is a standard questionnaire of leadership effectiveness and flexibility by Hersey and Blanchard. Data were analyzed using descriptive and non-parametric tests (Kruskal-Wallis, Fisher) through SPSS 17 software. Results: The results showed significant difference of leadership style from perspectives of managers and their subordinates based on Fisher test p=0.024. Conclusion: There is a significant difference between leadership style from perspective of managers and their subordinates that reflects the weakness of managers communicating with subordinates. Thus, providing feedback by subordinates can improve the relationship between managers and subordinate as well as increase the awareness of managers and their subordinates.